Ethnicity and Subjective Well-being in the Republic of North Macedonia. Issue 4 (4th July 2021) - Banerjee, Biswajit; Ball, Richard; Mughal, Abdul Ghaffar
ABSTRACT: This paper examines the nature of inter-ethnic relations in North Macedonia drawing on the 2008 European Quality of Life Survey. Ceteris paribus, the self-declared level of subjective well-being is smaller among ethnic Albanians than among Macedonians. In the presence of relative income variables, subjective well-being among both ethnic groups is not significantly associated with their absolute income. The subjective well-being of ethnic Albanians is significantly associated with their income relative to Macedonians. However, the subjective well-being of Macedonians is not affected by income relative to ethnic Albanians. The results suggest that measures are needed to reduce income inequality between ethnic groups.